A case study of the implementation of an ergonomics improvement committee in a Brazilian hospital – Challenges and benefits. (March 2016) - Bolis, Ivan; Sznelwar, Laerte I.
Abstract: This article discusses the creation of an improvement committee (IC) to implement policies aimed at improving working conditions in a public health institution in the city of São Paulo. Suggestions were proposed for future implementations of this organizational mechanism, pursuant to the presentation of the process of its formation and the main results achieved. The findings led to the conclusion that good outcomes require autonomy and support from management, and the adoption of effective measures to improve and legitimize the improvement committee's existence. Another important issue is facilitating worker involvement and creating a locus for dialog among people with different visions within the organization. Thus, two approaches converge: a top-down approach in which policies are defined and improvement actions are actually implemented based on a general outlook of the production and work system, and a bottom-up approach specific to employees who are also engaged in improvement policies and in putting them into practice. It is also possible to point out problems and opportunities arising from actual work situations to the higher levels of management. This kind of approach fits with macroergonomics, because it integrates strategy, organization and work issues. It is possible to discuss the benefits of this approach for companies and provide conditions for workers to engage effectively in these processes. In conclusion, these proposals can be considered from an emancipatory perspective, given that different actors should be able to codetermine working conditions and work content, thus directly influencing their individual and collective experiences. The support and commitment of upper management are essential elements of success in maximizing the effectiveness of this organizational approach. Highlights: Improvement committees (ICs) can elevate the discussion of ergonomics in the organizational structure. ICs allow workers to engage effectively in these processes, in an emancipatory perspective. ICs do not have to provide answers for everyone, but should be of a more political nature. ICs should be given strategic prominence in order to facilitate ergonomic changes.